2011
DOI: 10.1108/14626001111127133
|View full text |Cite
|
Sign up to set email alerts
|

Strategic governmental economic activities in support of young French SMEs

Abstract: Purpose -The purpose of this paper is to closely study young French small and medium enterprises (SMEs). The authors highlight the structure of these target firms and build a typology of corresponding business models. Design/methodology/approach -The authors used a dataset of 38,000 young French SMEs. It is constituted of all individual and consolidated year-end financial statements submitted by French firms to the commercial court. Data analysis techniques (principal component analysis then hierarchical and a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0
1

Year Published

2013
2013
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 9 publications
(11 reference statements)
0
5
0
1
Order By: Relevance
“…Entrepreneurship has often been regarded as a career choice made by teenagers and young adults around the age of twenty (Branchet, Augier, Boissin, & Quere, 2011;Nyock Ilouga, Nyock Mouloungni, & Sahut, 2014). On the other hand, some studies have found relatively more seniors engaged in entrepreneurship.…”
Section: Résumémentioning
confidence: 99%
See 1 more Smart Citation
“…Entrepreneurship has often been regarded as a career choice made by teenagers and young adults around the age of twenty (Branchet, Augier, Boissin, & Quere, 2011;Nyock Ilouga, Nyock Mouloungni, & Sahut, 2014). On the other hand, some studies have found relatively more seniors engaged in entrepreneurship.…”
Section: Résumémentioning
confidence: 99%
“…This is especially true when one considers the substantial efforts devoted in the last decade to the development of a sense of entrepreneurship among students. High schools, universities, and incubators have all been especially encouraged to help students create projects and facilitate their professional ambitions (Branchet et al, 2011). Relatively speaking, the entrepreneurial aspirations among seniors have been underemphasized.…”
Section: Applied Implicationsmentioning
confidence: 99%
“…Over the past decade, research and training opportunities in entrepreneurship increased strongly in service education. Encouraging universities, high schools, incubators and entrepreneurial networks to coordinate and develop common tools to reach the students is the core of public policy in developing entrepreneurship within this particular population as well as helping them to build their career plans and improving their employability (Branchet et al, 2011). A choice of career becomes especially crucial because of the current economic difficulties.…”
Section: Introductionmentioning
confidence: 99%
“…
Developing entrepreneurship among students and helping them to build their career plans and improving their employability is the core of public policy in a lot of countries in Europe (Branchet et al, 2011). Following some empirical researches (Boissin et al, 2009), we do know some predictive factors for the emergence of an entrepreneurial project.
…”
mentioning
confidence: 99%
“…It is a career options for youth and graduates [26,27] by providing employability. It reduces social ills and public policy makers are emphasizing and engaging students of higher learning institution in entrepreneurship to improve employability rate [28]. This has made research works on entrepreneurship phenomena very attractive, more so in how to attract graduate students towards entrepreneurship.…”
Section: Entrepreneurship Career Intentionmentioning
confidence: 99%